Pengaruh Budaya Perusahaan Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan - Susanto, Bambang Sujagad (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2013)
This study aimed to obtain information relating to whether the job satisfaction of employees affected by corporate culture and work motivation. Survey method used in this study was analyzed by regression analysis. In this study, the employees selected as the unit of analysis of 90 samples randomly selected. The analysis showed that the corporate culture and work motivation positive direct effect on job satisfaction, and simultaneously the corporate culture and work motivation positive effect on job satisfaction. Therefore, job satisfaction, corporate culture and work motivation should be incorporated into the strategic planning of human resources. Yet another variable that is required to be taken into account by the next academic researchers.